Reduced graphene oxide as a stable and high-capacity cathode material for Na-ion batteries - Ali, Ghulam; Mehmood, Asad; Ha, Heung Yong; Kim, Jaehoon; Chung, Kyung Yoon (NATURE PUBLISHING GROUP, 2017)
We report the feasibility of using reduced graphene oxide (RGO) as a cost-effective and high performance cathode material for sodium-ion batteries (SIBs). Graphene oxide is synthesized by a modified Hummers' method and reduced using a solid-state microwave irradiation method. The RGO electrode delivers an exceptionally stable discharge capacity of 240 mAh g(-1) with a stable long cycling up to 1000 cycles. A discharge capacity of 134 mAh g(-1) is obtained at a high current density of 600 mA g(-1), and the electrode recovers a capacity of 230 mAh g(-1) when the current density is reset to 15 mA g(-1) after deep cycling, thus demonstrating the excellent stability of the electrode with sodium de/intercalation. The successful use of the RGO electrode demonstrated in this study is expected to facilitate the emergence of low-cost and sustainable carbon-based materials for SIB cathode applications.
Keywords: ELECTRONIC-STRUCTURE RECOVERY; RAY-ABSORPTION-SPECTROSCOPY; ANODE MATERIAL; CHEMICAL-REDUCTION; POSITIVE ELECTRODE; SUPERIOR ANODE; CARBON; PERFORMANCE; NANOSHEETS; STABILITY